Nutritional status of Indigofera zollingeriana forage at different level draught stress and cutting interval - Herdiawan, Iwan; Abdullah, Luki; Sopandi, D (Indonesian Animal Sciences Society, 2014)
The low rainfall and high temperature greatly affect the decline in production and quality of forage in general. The experiment was arranged in a completely randomized design with two factors and four replications. The first factor consisted of 3 level of drought stress namely: 100% field capacity (FC) (control), 50% FC, and 25% FC. The second factor comprised of 3 defoliation interval i.e. interval defoliations of 60, 90 and 120 days. The observed variables were nutrient content (crude protein (CP), crude fibre (CF), Gross energy, lignin, selulose, neutral/acid detergent fibre (NDF/ADF), in vitro dry matter and organic matter digestibility (IVMD/IVOMD), Ash, Ca and P) and anti-nutrient content (Tannin and Saponin). Data were analyzed by ANOVA and the differences between treatments were tested by LSD. The results shows that there were interactions (P<0.05) between drought stress and defoliations interval on CP, CF, energy, cellulose, lignine, NDF/ADF, IVMD and IVOMD, but not to ash, Ca, P, saponin and tannin content. Drought treatment significantly (P<0.05) decreased CP, energy, IVMD and IVOMD, but CF, lignin, cellulose, ND/ADF, IVDMD/IVOMD, saponin and tannin increases. Defoliation interval significantly (P<0.05) decreases on CP, CF, energy, lignin, cellulose, NDF/ADF, and IVDMD/IVOMD, but saponin and tannin content did not affected. Key Words: I. zollingeriana, Drought Stress, Defoliation Interval, Nutrient, Anti-Nutrients